ОСОБЛИВОСТІ МАГНІТНОГО ЗВ’ЯЗКУ МІЖ ІНДУКТИВНОСТЯМИ ВИВОДІВ ВХІДНИХ І ВИХІДНИХ КОНДЕНСАТОРІВ У ПРОТИЗАВАДНИХ ФІЛЬТРАХ - Гурін, В.К.; Павловський, В.О.; Юрченко, О.М. (Інститут електродинаміки НАН України, Київ, 2013)
It is considered in the article the magnetic coupling between inductances of input and output capacitors’ leads for capacitors reducing differential mode noise in key-type power supplies. It is showed that the magnetic coupling mentioned above significantly reduces the insertion loss at frequencies above 0,50–1 MHz. It is investigated mutual-perpendicular arrangement of those capacitors as a method of reducing the magnetic coupling, and showed that such an arrangement increased the insertion loss of the filter for differential mode noise about 20 dB in the frequency range 1...20 MHz. References 9, figures 5.